2011
DOI: 10.2218/ijdc.v6i1.187
|View full text |Cite
|
Sign up to set email alerts
|

Are you Ready? Assessing Whether Organisations are Prepared for Digital Preservation

Abstract: In early 2009 the Planets project undertook a survey of national libraries, archives, and other content-holding organisations in Europe to better understand the organisations' digital preservation activities and needs, and to ensure that Planets' technology and services are designed to meet them. Over 200 responses were received including a cross-section of major libraries and archives especially in Europe. The results provide a snapshot of organisations' readiness to preserve digital collections for the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Documentation of organisational policies is often scarce; this is beginning to change [69]. Often, the first time evaluation and selection is carried out, a number of organisational factors have to be established once, which adds to the effort needed for the first decision process.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of organisational policies is often scarce; this is beginning to change [69]. Often, the first time evaluation and selection is carried out, a number of organisational factors have to be established once, which adds to the effort needed for the first decision process.…”
Section: Discussionmentioning
confidence: 99%
“…Sinclair and colleagues surveyed 172 national libraries, archives, and other cultural heritage organizations in Europe to "better understand the organization's digital preservation activities and needs." 14 While the respondents expressed a high level of awareness of the challenges of preservation, the authors found no corresponding level of policy and budgetary development. An Educause Center for Applied Research study by Yanosky examined data management in U.S. higher education.…”
Section: Institutional Context and Challenges Of Digital Asset Managementioning
confidence: 94%
“…As DP standards, methods, and concepts developed, organizations began to invest resources to meet their preservation needs. Interest and focus in recent years has subsequently extended from technical DP research and prototypes for individual tools, techniques, or system components to the deployment and operation of full‐fledged archival information systems (Atkins, Goethals, Kussmann, Phillips, & Vardigan, ; McKinney, Benson, & Knight, ; Sinclair et al, ). To evaluate how these solutions work in aggregate, an organizational view is needed.…”
Section: Introductionmentioning
confidence: 99%